Structural Instruments – the New Challenge for Romania. Investment Fields and the Beneficiaries for the Operational Programs 2007-2013 - Tatiana Mosteanu; Meral Ibraim (Theoretical and Applied Economics, 2007)
One of the most discussed subjects after Romania entered the family of EU is about the absorbtion and allocation of the European Funds allocated using the Structural Instruments. The forecasts show that the maximum level of absorbtion of EEU’s funds is about 3.7893% from GDP. In Romania case the European Funds will be allocated for convergence, for cohesion fund and for teritorial cooperation, the largest amount being allocated for the convergence criterion. From this amount dedicated to this criterion (19.668 billion Euro) a share wil be cofinanced by the national funds, both private and public (total amount for national cofinance is about 5.07 billion Euro). Other criterion of grouping the European funds ist hat of Operational Programs for the followig domains: the increase of economical competition, transportation, environment, regional, human resources development and technical assistance. We expect to see if the forecasted level for absorbtion of European Funds was well done.